Television Viewing Does Not Have to Be Sedentary: Motivation to Participate in a TV Exercise Program - Jessie J. M. Meis; Stef P. J. Kremers; Martine P. A. Bouman (Journal of Obesity)
The present study explored which underlying motivations induced people to participate in a television exercise program called “The Netherlands on the Move!-television” (NOM-tv). A cross-sectional study was carried out among 1,349 viewers of NOM-tv. The respondents completed the intrinsic motivation inventory (IMI), assessing their levels of intrinsic motivation towards participating in the NOM-tv exercises. The results showed that higher levels of intrinsic motivation (i.e. enjoying the NOM-tv exercises, feeling competent to perform this activity, and willingness to put effort into the exercises) were the most important predictive factors of more frequent participation in the NOM-tv exercises. Future screen-based interventions to reduce sedentary behavior should aim especially at encouraging people's intrinsic orientations towards physical activity in an autonomy-supportive way.